Current Hepatitis A Status in Canada - Jun Wu; Shimian Zou; Antonio Giulivi (Canadian Journal of Infectious Diseases)
Hepatitis A, caused by the hepatitis A virus, occurs most frequently in developing countries, but also causes sporadic cases or outbreaks in industrialized countries. The most common route of transmission is fecal-oral. The incidence of hepatitis A varies with geography, and economic and environmental conditions. The epidemiological pattern of the disease has changed with improvements in hygiene and economic conditions. The incidence and prevalence of hepatitis A has decreased, while the average age of exposure and subsequent infection has increased. The present report describes the current status of hepatitis A in Canada. The incidence rate of reported cases in Canada varies from over 10/100,000 (1991) to 3.6/100,000 (1998), and is higher in males, 4.7/100,000 (1998), than in females, 2.5/100,000 (1998). The highest reported hepatitis A rates are in age groups 30 to 39 years and 40 to 59 years, and in British Columbia. Such information is important for assessing current immunization approaches and for decision-making about new preventive strategies against hepatitis A in Canada.